2017
DOI: 10.18203/issn.2454-5929.ijohns20173668
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of clinical profile of deaf mute children at tertiary care center

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Hearing is necessary to learn language, speech and to develop cognitive skills. Hearing helps in developing child to learn, recognize sounds, identify objects, events and internalize concepts. Effects of hearing loss on the development of child’s ability to learn, to communicate and to socialize can be devastating. The study is planned with the aim to study clinical profile of deaf mute children and to identify ‘socio-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…This is in comparison to a study by Pawde et al where the most common health problems in deaf and mute children were pneumonia (10%), jaundice (10%), tonsillitis, exanthematous fever, and refractive errors. 12 A high proportion of children in the present study had dental caries (74%) compared to the study by Goud et al where the prevalence of dental caries was 49.3%. 13 But in contrast, Tefera et al found the prevalence of dental caries at 38.6%.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This is in comparison to a study by Pawde et al where the most common health problems in deaf and mute children were pneumonia (10%), jaundice (10%), tonsillitis, exanthematous fever, and refractive errors. 12 A high proportion of children in the present study had dental caries (74%) compared to the study by Goud et al where the prevalence of dental caries was 49.3%. 13 But in contrast, Tefera et al found the prevalence of dental caries at 38.6%.…”
Section: Discussioncontrasting
confidence: 61%
“…If no rehabilitation is done child develops physical and mental issues. 5,6 Improved survival rates, more advanced medical care, and increased longevity contribute to the increased number of disabled individuals. The greatest challenge that peoples with disability have to face is a societal misconception, i. e.; that they are a 'breed apart'.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, there were 66.7% males and 33.3% females with male to female ratio of 2:1. Such male predominance is widely [9] [10]…”
Section: Discussionmentioning
confidence: 99%
“…Our study depicted the scenario in rural central India in contrast to the abovementioned ones in the northern region and in Alexandria and Tanzania. [ 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…This signifies different approaches of the region and overall lack of awareness and concern regarding the early ENT examination and sensitization of doctors regarding the aspect of hearing loss. [ 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%